2020
DOI: 10.1038/s41380-020-0853-y
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal volume and hippocampal neuron density, number and size in schizophrenia: a systematic review and meta-analysis of postmortem studies

Abstract: Reduced hippocampal volume is a consistent finding in neuroimaging studies of individuals with schizophrenia. While these studies have the advantage of large sample sizes, they are unable to quantify the cellular basis of structural or functional changes. In contrast, postmortem studies are well suited to explore subfield and cellular alterations, but low sample sizes and subject heterogeneity impede establishment of statistically significant differences. Here we use a meta-analytic approach to synthesize the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
28
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 90 publications
7
28
2
Order By: Relevance
“…The present results, along with post-mortem evidence for cellular and biochemical changes in human hippocampal area CA4 (75-77) support future investigation into vMC function in rodent models for ventral hippocampal hyperactivation and cognitive deficits seen in schizophrenia. A key goal is to determine why vMC inhibition or excitation impairs spatial encoding.…”
Section: Discussionsupporting
confidence: 75%
“…The present results, along with post-mortem evidence for cellular and biochemical changes in human hippocampal area CA4 (75-77) support future investigation into vMC function in rodent models for ventral hippocampal hyperactivation and cognitive deficits seen in schizophrenia. A key goal is to determine why vMC inhibition or excitation impairs spatial encoding.…”
Section: Discussionsupporting
confidence: 75%
“…Previous research has demonstrated that the hippocampus is a key substrate for pathophysiological alterations in psychosis ( Allen et al, 2016 ; Cao and Cannon, 2020 ; Lieberman et al, 2018 ; Lodge and Grace, 2011 ; McHugo et al, 2019 ; Schobel et al, 2013 ; Vargas et al, 2018 ). Independent evidence also suggests that cellular neuropathology may be evident in the left rather than right hippocampus in schizophrenia ( Roeske et al, 2020 ). As such, previous magnetic resonance spectroscopy (MRS) studies have commonly acquired data from the left hippocampus ( Bossong et al, 2019 ; Briend et al, 2020 ; Merritt et al, 2016 ; Shakory et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Strong Zswim6 expression is detected in the CA1 and CA3 of the hippocampus. The hippocampus is known to be involved in the pathogenesis of schizophrenia (Ho et al, 2017;Roeske et al, 2020). Interestingly, Zswim6 is expressed in the medial habenula in which the schizophrenia-risk gene ErbB4 is also highly expressed (Steiner et al, 1999).…”
Section: Discussionmentioning
confidence: 99%